2007
DOI: 10.1002/ijc.22921
|View full text |Cite
|
Sign up to set email alerts
|

IGF‐1 and IGFBP‐3: Risk of prostate cancer among men in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial

Abstract: IGF-1 and IGFBP-3 may influence risk of prostate cancer through their roles in cellular growth, metabolism and apoptosis, however, epidemiologic results have been inconsistent. The role of obesity in prostate cancer risk is not clearly understood, but hyperinsulinemia-related increases in bioactive IGF-1 levels, associated with obesity, could be a component of the relationship between the IGF-axis and prostate cancer. We conducted a nested case-control study in the prospective Prostate, Lung, Colorectal and Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 68 publications
(80 reference statements)
4
26
1
2
Order By: Relevance
“…Insulin and IGF are known to regulate cell cycle progression, growth, proliferation, metabolism and over all cell survival. There is strong evidence of IGF and insulin pathway dysregulation in several cancers including breast [47, 48], prostate, colon and pancreatic cancers [49]. Several therapies have been directed towards inhibiting IGF-1R signaling with the objective of preventing cancer progression [50].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin and IGF are known to regulate cell cycle progression, growth, proliferation, metabolism and over all cell survival. There is strong evidence of IGF and insulin pathway dysregulation in several cancers including breast [47, 48], prostate, colon and pancreatic cancers [49]. Several therapies have been directed towards inhibiting IGF-1R signaling with the objective of preventing cancer progression [50].…”
Section: Discussionmentioning
confidence: 99%
“…Another large case-control study has indicated that metformin may somewhat reduce the incidence of pancreatic cancer (15). Early-stage clinical trials are currently underway to investigate the potential of metformin to prevent an array of cancers, including colorectal, prostate, endometrial and breast cancer (1618). However, the underlying mechanism remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Among the molecules secreted by the tumor microenvironment, the growth factor IGF-I plays an important role in development and progression of various human cancers, and also in the inhibition of apoptosis (19). Elevated plasma concentrations of IGF-I has been linked to a high risk for several types of cancers including breast, prostate and lung cancer (20,21). In this study, using several techniques (Table II) we showed that Hospicells secrete IGFs and IGF related proteins.…”
Section: Discussionmentioning
confidence: 99%